ATTRIBUTES OF THE BOARD OF COMMISSIONERS AND CORPORATE RISK (Banking On The Indonesia Stock Exchange) - Natatsa Rizqina Mubarika; Rr. Sri Handayani (Jurnal Reviu Akuntansi dan Keuangan, 2019)
The aim of this study is to examine board of Commissioners’ atributes to firm risk. Firm risk is measured using accounting and market data. Firm risk is measures used in this study are total risk and asset return risk. The independent variable in this study is the board of commissioners’ attributes which consist of board size, the independence, gender diversity, age, tenure, attendance and frequency of audit meetings. This study used systematic sampling to determined sample and population of this study is conventional banking companies listed on the Indonesia Stock Exchange for the period 2014-2017. Multiple linear regression analysis is used as a hypothesis testing and the sample used is 116 conventional banking companies.The result showed that board size and gender diversity have a positive and significant effect on firm risk. While board age and the frequency of audit committee meetings have a negative and significant effect on firm risk.